Kajian Drug Related Problems (DRPs) terhadap Pengobatan ISPA pada Pediatri di Klinik Pratama Kabupaten Bogor Periode Januari-Desember 2021 - Notiasary, Marina; Siregar, Tahoma (LPPM, INSTITUT SAINS DAN TEKNOLOGI NASIONAL, 2025)
Drug Related Problems (DRPs) is a form of pharmaceutical service that looks for all drug-related problems in a treatment. The prevalence of Acute Respiratory Infection (ARI) in pediatrics in the 2019 Bogor District Health Profile report is still quite high, coupled with the high number of pediatric hospitalizations with ARI, making it one of the highest causes of death in pediatrics. This study aims to examine DRPs for the treatment of ARI in Pediatrics at the Primary Clinic, Bogor Regency in 2023. The method used in this research is a retrospective descriptive by reviewing patient medical records in 2021 with a purposive sampling design on 87 prescriptions with 555 prescribed drugs, the highest results showed that 84 (96.6%) prescriptions and 277 (50%) drugs experienced DRPs. Sample characteristics based on age in the 2 year-<12year category 55 (63.2%), the most gender was male 49 (56.3%), the most weight was in the thin category 48 (55.2%) and comorbidities as many as 17 (19.3%). The drug use profile includes the drug classes Antibiotics, Analgesics – Antipyretics, Antihistamines, Corticosteroids, Decongestants, Bronchodilators, Mucolytics/Expectorants, Antitussives, Combination drugs and Additional therapy. Conclution of Drug Related Problems (DRPs) Study at the Primary Clinic, Bogor Regency in 2021 in the category of Polypharmacy 78 (89.7%), Low Doses 252 (45.4%), High Doses 25 (4.5%), Indications without Drugs 14 (16.1%), Drugs Without Indications 18 (3, 4%), Potential for Drug Interaction with Drugs Most Moderate 144 (44%).